Przestępstwo pospolite czy podatkowe? Zbieg czynów zabronionych w rozumieniu art. 8 § 1 k.k.s. w świetle najnowszego orzecznictwa Sądu Najwyższego - Piątkowska, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Mechanisms of VAT fraud are discussed mainly through the prism of the problems of the legal qualification of such offenses, which have been for many years the subject of disputes in the doctrine, as well as the subject of the discrepancies in the judgments of the common courts and the Supreme Court. Relationships existing between the offence under Article 286 § 1 of the Penal Code and the fiscal offence under Article 76 § 1 of the Penal Fiscal Code appear in court decisions and are relating to ideal concurrence of punishable acts set in the Article 8 § 1 of the Penal Fiscal Code.The author of the article conducts an analysis of the construction of the ideal concurrence of punishable acts in the light of doctrine, most frequently cited jurisdictions and the latest Resolution of the Supreme Court adopted on the 24th January 2013.Choosing a certain legal qualification implies serious consequences not only on the procedural grounds, including issuing an arrest warrant and a severe punishment. It also implies different models of crime prevention and co-operation between financial and non-financial State agencies and bodies.
Keywords: VAT; podatki; wyłudzenie; czyny zabronione